The Hidden Impacts of Phosphorus Pollution to Streams and Rivers. (19th February 2020) - Mallin, Michael A; Cahoon, Lawrence B
Abstract: Phosphorus (P) enrichment to streams, lakes, and estuaries is increasing throughout the United States. P loading is typically viewed from a harmful algal bloom perspective; if added P causes excess growths of phytoplankton or macroalgae, it may become targeted for control. However, P loading also contributes to two other non–algae-based aquatic problems. Field and experimental evidence shows that P loading directly stimulates growth of aquatic bacteria, which can increase to concentrations that exert a significant biochemical oxygen demand on water bodies, contributing to hypoxia, a widespread impairment. Experimental evidence also demonstrates that fecal bacterial growth can be significantly stimulated by P loading, increasing health risks through exposure or the consumption of contaminated shellfish and causing economic losses from beach and shellfish area closures. Resource managers need to look beyond algal bloom stimulation and should consider the broader roles that excess P loading can have on ecosystem function and microbiological safety for humans.